2018
DOI: 10.1080/15230430.2018.1495445
|View full text |Cite
|
Sign up to set email alerts
|

Topographic influences on ring widths of trees and shrubs across alpine treelines in southwest Yukon

Abstract: Growth responses of trees and shrubs to climate often exhibit unexplained variation in alpine regions, making it difficult to predict how they will respond to future changes in climate. We sought to characterize and explain this variability in southwest Yukon, a topographically complex region of subarctic Canada. We collected cores and sections from 360 spruce trees and 480 willow shrubs across treelines on north and south aspects in six valleys spanning two mountain ranges. We compared growth rates, growth pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…These differences are likely leading to colder temperatures and shorter growing seasons at QN. Significantly higher inter‐series correlations (rbar) on the west‐facing slope also suggest (Dearborn and Danby, ) that growth patterns at QW would be more governed by broad‐scale climatic patterns influencing growth of all individuals. At QN, by contrast, we hypothesize that microtopography may induce substantial spatial variability in shrub growth as previously observed in topographically complex regions (Danby and Hik, ; Leonelli et al., ; Ropars et al., ; Young et al., ; Dearborn and Danby, ).…”
Section: Discussionmentioning
confidence: 88%
“…These differences are likely leading to colder temperatures and shorter growing seasons at QN. Significantly higher inter‐series correlations (rbar) on the west‐facing slope also suggest (Dearborn and Danby, ) that growth patterns at QW would be more governed by broad‐scale climatic patterns influencing growth of all individuals. At QN, by contrast, we hypothesize that microtopography may induce substantial spatial variability in shrub growth as previously observed in topographically complex regions (Danby and Hik, ; Leonelli et al., ; Ropars et al., ; Young et al., ; Dearborn and Danby, ).…”
Section: Discussionmentioning
confidence: 88%
“…Cross-dating was statistically validated using the software COFECHA (Tree-Ring Lab, Colombia University). Each series was individually detrended with the program ARSTAN (Tree-Ring Lab, Colombia University) using either a negative-exponential curve or linear regression line (Dearborn and Danby 2018 ). Ring-width series from 7–9 shrubs in each habitat-type were selected as the most confidently cross-dated, and then averaged to yield master chronologies for each habitat-type.…”
Section: Methodsmentioning
confidence: 99%
“…2) which could lead to different soil moisture at the site level. Study in the alpine treeline sites in Yukon also showed that willow shrub growth variation is influenced by the soil moisture content in early growth season (Dearborn & Danby, 2018).…”
Section: Discussionmentioning
confidence: 95%